Contesting precarity in Japan the rise of nonregular workers and the new policy dissensus - Shibata, Saori, 1973- (ILR Press, an imprint of Cornell University Press, 2020)
"Drawing on a new dataset charting protest events from the 1980s to the present, this book produces a systematic study of the new precarious labor movement that has developed during Japan's post-bubble neoliberal economic transformation"--